Dynamic response sensitivity of an offshore wind turbine for varying subsoil conditions. (1st June 2015) - Damgaard, M.; Andersen, L.V.; Ibsen, L.B.
Abstract: In this paper, a comprehensive study is performed on the dynamic response of an offshore wind turbine installed on a monopile. The aim is to evaluate to what extent a change of the soil properties affects the fatigue loads for parked conditions. Based on consistent lumped-parameter models calibrated to semi-analytical impedance functions of a monopile embedded in a linear viscoelastic soil layer, fully coupled aero-hydro-elastic simulations are conducted in the nonlinear multi-body code Hawc 2. Correlation of wind speeds and waves is derived on basis of wind–wave scatter diagrams from the North Sea. Changes of the soil stiffness, the soil damping and the presence of sediment transportation at seabed are shown to be critical for the fatigue damage equivalent moment at mudline that may change with more than 30% for parked wind turbine conditions. Abstract : Highlights: Sensitivity analysis between fatigue loading and soil properties is conducted. Soil stiffness and soil damping have a high impact on the equivalent moment at mudline. Sediment transportation turns out to increase the fatigue loading tremendously.